DIVERSITAS PANGAN POKOK DALAM SEJARAH KEBIJAKAN PANGAN DI INDONESIA - Joshua Jolly Sucanta Cakranegara (Balai Pelestarian Nilai Budaya Kalimantan Barat, 2022)
This article aims to explain the history of food policy in Indonesia related to the diversity of staple foods in 1945-2021. This research used historical methods and literature studies on food policy studies. The results indicate that no continuity of staple food diversity which is the historical reality of contemporary Indonesian food policy. In the beginning, the diversity of staple food, the local wisdom of the archipelagic community, had received a considerable attention in the idealism of President Sukarno. However, it still was not fulfilled in the next period, such as in the rice politics of President Soeharto, the food security movement of President Megawati Soekarnoputri, the food import policy of President Susilo Bambang Yudhoyono, to the food barn policy of President Joko Widodo. The diversity of staple foods in contemporary government policies is accommodated in short-term, local, or partial scale programs, and not adaptive to changing times. Thus, the fulfillment of community’s staple food is still dominated by non-inclusive food policies.